2005
DOI: 10.1002/mats.200400109
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of ABCD Tetrablock Copolymers Predicted by Self‐Consistent Field Theory

Abstract: Summary: We studied the two‐dimensional (2D) microphase‐separated morphology of linear ABCD tetrablock copolymers by self‐consistent field theory. By varying the interaction parameters and the compositions, we found at least twelve structures, two of which – “four‐color” lamellae and “three‐color” core‐shell hexagonal phase – prove the existing experimental observations. These morphologies were discussed in correlation with the volume fraction of the components and the interaction parameters. A specific behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…2 have such a high symmetry. But when it comes to the linear copolymers, situations change [28]. There are many different morphologies like LAM 4 (''four-color lamellae''), CSH (coreeshell hexagonal lattice), CST 2 (coreeshell two interpenetrating tetragonal lattice), LAM þ BD (lamellae with beads inside), CS 3 H (''threecolor'' coreeshell hexagonal phase), LAM þ BD 2 (lamellae with ''two-color'' beads inside).…”
Section: Ordered Microphases Of Abcd 4-miktoarm Block Copolymer Witmentioning
confidence: 97%
See 2 more Smart Citations
“…2 have such a high symmetry. But when it comes to the linear copolymers, situations change [28]. There are many different morphologies like LAM 4 (''four-color lamellae''), CSH (coreeshell hexagonal lattice), CST 2 (coreeshell two interpenetrating tetragonal lattice), LAM þ BD (lamellae with beads inside), CS 3 H (''threecolor'' coreeshell hexagonal phase), LAM þ BD 2 (lamellae with ''two-color'' beads inside).…”
Section: Ordered Microphases Of Abcd 4-miktoarm Block Copolymer Witmentioning
confidence: 97%
“…Meanwhile, many morphologies occurred in the present case disappear, such as, HEX, HEX 2 , HEX 3 , HEX 3i , TET 2 , TET 3 , TET 4 , HEX þ PEP 2 , and HEX þ TET 2 . That shows that the morphology not only depends on the composition of the block copolymer but also relies on its architecture [28].…”
Section: Ordered Microphases Of Abcd 4-miktoarm Block Copolymer Witmentioning
confidence: 98%
See 1 more Smart Citation
“…Takano et al reported a noncentrosymmetric lamellar structure of an ABCA terpolymer, while an O 52 network structure was reported for a tetrablock terpolymer of the ABAC type . Moreover, a four-phase lamellar structure has been found for an ABCD tetrablock quarterpolymer, whereas complex morphologies have been predicted for an ABCD quarterpolymer by SCFT . Furthermore, Meuler et al reported on the O 70 ( Fddd ) network structure of a pentablock terpolymer of the ABCBA type …”
mentioning
confidence: 99%
“…14 Moreover, a four-phase lamellar structure has been found for an ABCD tetrablock quarterpolymer, 15 whereas complex morphologies have been predicted for an ABCD quarterpolymer by SCFT. 16 Furthermore, Meuler et al reported on the O 70 (Fddd) network structure of a pentablock terpolymer of the ABCBA type. 17 On the other hand, star-shaped terpolymers of the ABC type have very peculiar structures due to their restricted molecular architectures, and they tend to have structures with assemblies of rods, whose cross sections can produce periodic tiling structures.…”
mentioning
confidence: 99%